Final orientation for new graduates on the highest attainable standard of health - Samlee Plianbangchang (Journal of Health Research, 2019)
Purpose - The purpose of this paper is to discuss the importance of taking responsibility for our own self-care as fundamental to achieving optimum healthcare at all levels: family, community and country. However, for self-care to work at its best, the support of the government and the national medical and public health workforce are required in addition to increased facilities that ensure the development and long-term maintenance of a person’s health status. Moreover, inter-disciplinary government policy, strategy and resource support should be placed as a central part of the national healthcare development system. Design/methodology/approach - It is a commentary piece of work from own long experience in working with the World Health Organization. Findings - The value of self-care and individual responsibility in achieving one’s own good health ultimately results in improved national and global health standards. Originality/value - This commentary explores the ideas and concepts on ways and means of leading people to think and act toward achieving their own optimum health in order to lead a socially and economically productive life and ultimately achieve “the highest attainable standard of health,” a WHO objective.